'You can't be careful enough': Measuring interpersonal trust during a pandemic. Issue 2 (3rd July 2021) - Wollebæk, Dag; Fladmoe, Audun; Steen-Johnsen, Kari
ABSTRACT: Empirical results regarding the role of interpersonal trust in the pandemic setting have been inconsistent. We argue that one explanation may be an inherent weakness in the standard measure of generalised trust, requesting respondents to choose between the options 'most people can be trusted' and 'you can't be careful enough in dealing with people'. The item measures two inter-related yet separate dimensions - trust and caution. A sense of caution is likely to be activated within the pandemic; some respondents may interpret 'being careful' as avoiding infection or spreading the virus. This may lead to 1) exaggerated negative trends in trust after the pandemic outbreak and 2) misrepresentation of the relationship between trust and compliance with guidelines. This is more likely to occur if respondents are primed to think about the pandemic. Analyses of several survey data sets from Norway confirmed that the standard question showed a decline in trust levels after the pandemic outbreak and a weakly negative correlation with social distancing. Alternative operationalisations without reference to caution suggested a small increase in trust and neutral or a weakly positive correlation with social distancing. Our results imply that the standard question should be used with caution in pandemic research.